Comparison of the enzymatic efficiency of Liberase TM and tumor dissociation enzyme: effect on the viability of cells digested from fresh and cryopreserved human ovarian cortex - Viola Maria Schmidt; Vladimir Isachenko; Gunter Rappl; Gohar Rahimi; Bettina Hanstein; Bernd Morgenstern; Peter Mallmann; Evgenia Isachenko (Reproductive Biology and Endocrinology, 2018)
Abstract Background The aim of this study was to examine the effectiveness of Tumor Dissociation Enzyme (TDE) on the viability of follicles after digestion of fresh and cryopreserved ovarian cortex fragments (OCFs). Methods Fresh and thawed OCF from 14 patients (29 ± 6 years), sized 20 to 210 mm3 were randomly distributed into four treatment groups and digested with 16% TDE or 0.05 mg/ml Liberase TM: Group 1, frozen OCF digested with TDE; Group 2, frozen OCF digested with LiberaseTM; Group 3, fresh OCF digested with TDE; and Group 4, fresh OCF digested with Liberase TM. Evaluation of follicle viability was performed under light microscope after staining with Neutral red. For visualization of viable and dead cells under a confocal laser scanning microscope, the follicles were stained with Calcein AM and ethidium homodimer-1. Results The results showed that the number of retrieved follicles was significantly higher (990 vs 487; P < 0.01) in the TDE-treatment group compared to the Liberase TM-group. The presence of intense neutral red stained follicles was significantly higher in Group 1 and Group 3 compared to Group 2 and Group 4 (70.3% ± +/− 6.22 vs 53,1% ± 2.03 and 94.2% ± 6.6 vs 79.1% ± 2.1; P < 0.01). The percentage of Calcein AM stained follicles of class V1 was significantly higher in Group 1 and Group 3 compared to Group 2 and Group 4 (95.97% ± 7.8 vs 87.87% ± 2.4; 97.1% ± 6.8 vs 91.3% ± 2.3; P < 0.01). Conclusion The enzymatic digestion of ovarian cortex with TDE provides recovery of a higher number of healthy preantral follicles in contrast to earlier described Liberase TM procedure.